Capital Market Integration and Gender Inequality - Mizuki Komura; Hikaru Ogawa (Institute of Labor Economics (IZA), 2018)
This study explores the effects of globalization on gender inequality. Specifically, we depict that, in terms of capital market integration, globalization alters the gender gap in wage rates through changes in labor demand for capital-intensive sectors. Consequently, globalization leads to opposite effects on the couple's labor supply and fertility decisions in capital-importing and capital-exporting countries, via changes in the bargaining positions of men and women. Moreover, by considering the properties of the industrial structures of capital-importing and capital-exporting countries, our result shows that globalization induces empirically observed declines in fertility rates throughout the world.
Keywords: F15; F21; F66; J12; J13; J16; 330; globalization; capital market integration; gender inequality; domestic production